Dipyridamole activates adenosine A2B receptor and AMPK/cAMP signaling and promotes myogenic differentiation of myoblastic C2C12 cells - Marco-Bonilla, Miguel; Herencia, Raquel; Fresnadillo, María; Huete-Toral, Fernando; Carracedo, Gonzalo; Largo, Raquel; Herrero-Beaumont, Gabriel; Mediero, Aránzazu (Frontiers in Pharmacology, 2023)
Sarcopenia is defined as a loss of muscle mass and strength. ATP homeostasis is crucial during myogenesis. We determined how the purinergic system modulates myogenesis using dipyridamole (blocks adenosine taken up by the cells) and tenofovir (inhibits ATP release) in a myoblast cell line. C2C12 cells were differentiated in the presence/absence of tenofovir/dipyridamole, with/without the A2B selective inhibitor PSB-603. Extra-/intracellular nucleotides were examined viaHPLC. The expression of muscle differentiation proteins (Pax7, Mif5, MyoD, MyoG, and MHC), PKA/CREB, adenosine receptors (A1, A2A, A2B, and A3), ATP-channel pannexin-1 and the P2X7 receptor was analyzed via WB and RT-PCR. cAMP and AMPK activation was measured. Tenofovir increased intracellular ATP and reduced extracellular adenosine, decreasing Pax7 expression and increasing MHC expression prematurely. Dipyridamole increased intracellular AMP and extracellular adenosine, counteracting the premature myogenesis promoted by tenofovir. All adenosine receptors were expressed during differentiation with dipyridamole, increasing A2B expression. Tenofovir maintained inactive AMPK and decreased cAMP levels, as well as PKAα and pCREB expression, which were recovered with dipyridamole. Adenosine and ATP act as mediators in muscle myogenesis. The blockade of ATP release by tenofovir promotes premature myogenesis, with dipyridamole counteracting the premature differentiation promoted by tenofovir via the adenosine A2B receptor and cAMP/AMPK pathways. Therefore, dipyridamole might be of interest as a therapeutic approach in sarcopenia.